Problematika Ideologi Sekularisme dalam Pendidikan Tingkat Madrasah Tsanawiyah - Setiawan, Hendra; Minarti, Sri (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Secularism in Islamic education has become an issue that has received increasing attention in the context of education in Indonesia. This study aims to examine the impact of secularism in Islamic education at MTs Darut Tauhid Ngablak Bojonegoro. This research is based on the need to understand how secularism views affect the Islamic education process in the institution. The purpose of this study is to analyze the implications of secularism on student development and daily activities at MTs Darut Tauhid. The research method used is a qualitative approach with case studies supported by a literature review. Data was obtained through observation, interviews, and analysis of related documents. The results of the study show that the view of secularism in Islamic education in MTs Darut Tauhid has caused inadequacy in supervision and control over student activities, as well as affecting the interaction between students physically. The implications of these findings highlight the need for reforms in the epistemology of Islamic education based on spiritual values, monotheism, and scientific character from an Islamic perspective.